PERAN FAKTOR DEMOGRAFI DALAM PENGEMBANGAN HUTAN KOTA DI SUMATERA BAGIAN SELATAN - Edwin Martin; Bondan Winarno (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2014)
The main role of urban forest is to provide environmental services. Unfortunately, many cities in developing countries recently face challenges in expanding urban forest. One of the challenges is to synchronize population increment by integrating urban forest into city planning and development. Studies in developed countries showed that population density is an opportunity for developing urban forest. The aim of this research is to obtain knowledge about the role of demographic factor in relation to the development of urban forest. Micro and macro approach are used in this research. Macro approach compares the performance of urban forest among cities with different demography, while the micro approach finds out the different performance of urban forest among regions with different density of population in one city. The result indicates that population density contributes to inhibit and to support the development of urban forest. This population density, as demographic factor, should be considered in calculating the minimal area of urban forest needed in a city.